Chitosan and Keratin Hydrolysate Treatment of Archived Newsprint - AL- Karagholy, K. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study is focused on the modification of the standardized newspaper with natural polymers chitosan and keratin hydrolysate applied on the paper surface from polymer solution. This modification is based particularly on the formation of the complexes between acidic surface groups on cellulose fibers and the natural polymers which improved the mechanical properties of the paper and the positive results which were observed particularly in folding endurance of the newspaper.